Cross-cultural adaptation and validation of the STarT back screening tool in isiZulu - Peta-Ann Schmidt; Vaneshveri Naidoo (AOSIS, 2020)
Background: Non-specific low back pain (NSLBP) is one of the most prevalent conditions in the world. Identifying patients at risk for developing chronic NSLBP is key to effective treatment. The STarT back screening tool is a validated, prognostic screening tool identifying subgroups of NSLBP patients, and the risk factors associated with each subgroup, guiding treatment in the primary care of NSLBP. Objectives: To translate the English version of the STarT back screening tool into isiZulu and determine the content validity and reliability of the translated tool. Method: Translation was completed in four phases - forward translation and synthesis, backward translation and expert review. Validation included expert review for content validity and testing of the translated tool on 30 patients, determining test-retest reliability, internal consistency and usability. Results: Minor linguistic differences were addressed during the translation phase. Item content validity was excellent for relevance (1.00), satisfactory (0.94) for clarity, simplicity and ambiguity, with scale-content validity acceptable (0.955). Spearman's correlation coefficient for test-retest reliability was acceptable (0.73). Cronbach's alpha for internal consistency for the total score for test 1 and test 2 was 0.68 and 0.77, and for the psychosocial scale 0.62 and 0.77 respectively. Overall, 33% found the tool very easy to understand and 40% found it very easy to complete. Conclusion: The isiZulu STarT back screening tool showed excellent content validity, acceptable reliability and acceptable internal consistency. Clinical implications: Use of the isiZulu tool in local clinics and private practices can improve clinical decision-making and treatment outcomes for isiZulu-speaking patients with NSLBP.